PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN SISTEM PENGENDALIAN INTERN TERHADAP AKUNTABILITAS KEUANGAN PADA SKPD PEMERINTAH DAERAH DI KABUPATEN KERINCI - Rio Baviga (Gapenas Publisher, 2022)
This study analyzes the influence of the Regional Financial Accounting System and Internal Control System on Financial Accountability. All data used in the analysis are data obtained from observations, interviews and various literatures concerning the Regional Financial Accounting System and the Internal Control System for Financial Accountability at the Regional Government SKPD in Kerinci Regency. Based on research that the Regional Financial Accounting System affects the Regional Financial Accountability of Kerinci Regency, this is evidenced by t count> t table (5,091> 1,708), the Internal Control System has an effect on Kerinci Regency Regional Financial Accountability, this is evidenced by t count> t table (1,865> 1.708), Simultaneously there is a significant influence between the Regional Financial Accounting System and the Internal Control System on Financial Accountability in the SKPD of the Regency Government, which can be proven by F arithmetic > F table (31.219 > 3.42). And the magnitude of the influence of the Regional Financial Accounting System and Internal Control System on Financial Accountability in the SKPD of the Regency Government is 72%.